The endophyte Klebsiella pasteurii BDA134-6 isolated from African rice colonizes durum wheat plants helping them cope with water shortage stress - Maria Laura Amenta; Stefano Varriale; Salvatore Arbucci; Fabio Fania; Pasquale De Vita; Stephan Summerer; Angelo Petrozza; Roberto Defez; Carmen Bianco (Scientific Reports)
Abstract Plant growth-promoting bacteria (PGPB) represents a sustainable strategy to improve the adaptability of plants to water shortage stress. The present study demonstrated that the endophyte Klebsiella pasteurii BDA134-6, isolated from O. glaberrima rice grown in Mali (West Africa), efficiently colonized the durum wheat variety Primadur. Results obtained from laboratory growth chamber, greenhouse phenotyping platform, and tunnel-type greenhouse demonstrated that inoculated Primadur plants improved their response to water shortage stress. When water shortage stress was simulated by treatment with polyethylene glycol, neither a significant decrease in the relative water content of leaves nor a strong inhibition of acetylene reduction was observed for inoculated plants compared to the uninoculated ones. Inoculated plants subjected to water shortage stress showed increased activity of the antioxidant enzymes glutathione reductase and superoxide dismutase (up to 38% and 191%, respectively), a proline content 3-fold higher, a reduced hydrogen peroxide accumulation (up to 50%), and no significant alterations in lipids peroxidation and leaf senescence. These findings highlight that BDA134-6 is a promising strain. Field trial experiments will allow to evaluate whether it can be used to improve antioxidant defense systems in a plant species different from the native host plant.